Probe pin material and probe pin made of Ag-Pd-Cu alloy

JP7625115B6Active Publication Date: 2025-02-21TANAKA KIKINZOKU KOGYO KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024072821
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-02-21
Estimated Expiration
2044-04-26

Smart Images

  • Figure 0007625115000001_ABST
    Figure 0007625115000001_ABST
Patent Text Reader

Abstract

To provide a probe pin material made of a Ag-Pd-Cu alloy with high hardness due to efficient precipitation hardening. [Solution] The probe pin material is made of Ag, Pd, Cu, and an Ag-Pd-Cu alloy containing Zn, Sn, and B. These additive elements have a Zn concentration of 0.5% by mass to 2.5% by mass, a Sn concentration of 0.5% by mass to 2.5% by mass, and a B concentration of 0.05% by mass to 0.5% by mass. X, Y, and Z are located within a range surrounded by straight lines at points A1 to A4 in an XYZ pseudo ternary phase diagram, where X is the Ag concentration, Y is the Pd concentration, and Z is the Cu concentration + Zn concentration + Sn concentration + B concentration. Point A1 (X: 24% by mass, Y: 40% by mass, Z: 36% by mass) Point A2 (X: 34% by mass, Y: 40% by mass, Z: 26% by mass) Point A3 (X: 17% by mass, Y: 57% by mass, Z: 26% by mass) Point A4 (X: 7% by mass, Y: 57% by mass, Z: 36% by mass)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy material suitable for probe pins used in testing electric / electronic devices, semiconductor devices, etc. More specifically, the present invention relates to a probe pin material made of an Ag-Pd-Cu alloy containing predetermined additive elements, which is hardened by optimized age hardening to achieve a higher hardness than conventional materials. [Background technology]

[0002] Probe testing equipment equipped with a probe card is used to test the continuity and operating characteristics of elements mounted on the circuit boards of various electronic devices and the semiconductor wafers of semiconductor devices. A large number of probe pins are supported on the probe card, and testing is performed by contacting the probe pins with the electrodes of the elements, etc., to send and receive electrical signals between the electrodes.

[0003] Probe pins are used in harsh environments where they are repeatedly brought into contact with and separated from the electrode while electricity is being passed through them. Therefore, in addition to low electrical resistance as a conductive material, materials for probe pins are required to have mechanical properties such as hardness and springiness, as well as corrosion resistance and chemical stability. Of these various properties, hardness is particularly important, as it is the main property that affects the wear resistance of probe pins.

[0004] Several alloys have been proposed as materials for probe pins. For example, the applicant of the present application has proposed a precious metal-based alloy mainly composed of precious metals such as Pt and Au. These precious metal alloys are particularly excellent in wear resistance, and are known as high-hardness probe pin materials due to plastic processing and precipitation effects (Patent Documents 1 and 2).

[0005] In addition, Ag-Pd-Cu alloys are known as alloys that are often used as probe pin materials. The Ag-Pd-Cu alloy, which is the basis of this alloy, is a relatively low-resistance alloy, and can further exhibit an increase in hardness due to the PdCu phase (bcc structure), which is an intermetallic compound formed by aging precipitation. In addition, Ag-Pd-Cu alloys can improve properties such as oxidation resistance and workability by adding various additive elements (hereinafter, alloys with additive elements added to Ag-Pd-Cu alloys are referred to as Ag-Pd-Cu alloys). Due to these advantages, many applications of Ag-Pd-Cu alloys as probe pin materials have been reported.

[0006] Examples of probe pin materials made of Ag-Pd-Cu alloys include Ag-Pd-Cu alloys with In added as an additive element (Patent Document 3), Ag-Pd-Cu alloys with B added as an additive element (Patent Document 4), and Ag-Pd-Cu alloys with In and / or Zn added as additive elements (Patent Document 5). These Ag-Pd-Cu alloys aim to improve resistivity, hardness, and workability by specifying additive elements and optimizing the composition ratio of the constituent metals (Pd, Cu). In addition, the present applicant has also reported on Ag-Pd-Cu alloys (Patent Document 6). In this prior art, the present applicant has disclosed an Ag-Pd-Cu alloy with B added as a first additive element and at least one of Sn, Bi, and Zn added as a second additive element. The present applicant's Ag-Pd-Cu based alloy takes into consideration required properties such as resistance value and hardness, and also aims to improve bending resistance during processing of the probe pin. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4176133 specification [Patent Document 2] Patent No. 4216823 specification [Patent Document 3] International Publication No. WO2019 / 194322 [Patent Document 4] International Publication No. WO2019 / 130511 [Patent Document 5] Patent No. 4878401 Specification [Patent Document 6] Patent No. 7072126 specification Summary of the Invention [Problem to be solved by the invention]

[0008] As described above, the probe pin materials have been developed to date with consideration given to basic required characteristics such as hardness and low resistance, while also adding value such as improved processability and improving the balance between them. However, as described above, the most important requirement for the probe pin materials is hardness to ensure wear resistance. With an emphasis on hardness, the probe pin materials made of Ag-Pd-Cu alloys described in the above-mentioned prior art have a maximum hardness of about 550 Hv even after age hardening. In this regard, the applicant believes that there is still room for improvement in the hardness of Ag-Pd-Cu alloys.

[0009] Therefore, the present invention provides a probe pin material made of an Ag-Pd-Cu alloy that has a hardness higher than that of conventional materials. Specifically, the present invention provides a probe pin material made of an Ag-Pd-Cu alloy that can exhibit a Vickers hardness of 580 Hv or more by performing aging heat treatment. In achieving this objective, the present invention also takes into consideration the processability when processing the Ag-Pd-Cu alloy into the shape and dimensions required for a probe pin. [Means for solving the problem]

[0010] As described above, the Ag-Pd-Cu alloy is an age-hardening alloy whose hardness increases due to precipitation hardening caused by aging heat treatment. The reason why such age-hardening alloys are suitable as materials for probe pins is that the timing of hardening the alloy can be adjusted during the process from manufacturing (casting) to processing into a probe pin. Probe pins are manufactured from a wire-shaped material with a small wire diameter, and the tip of the probe pin may also be finely processed. For such high processing rates and processing that requires fine and accurate processing, it is preferable that the processed material is soft to a certain extent. In the case of age-hardening alloys, high hardness can be obtained while maintaining a near-shape state by processing them in a soft state before aging and then performing aging heat treatment.

[0011] Therefore, in order to achieve the high hardness that is the subject of the present invention while considering the workability, it depends on how to increase the difference in hardness before and after the aging heat treatment. In other words, it is necessary to increase the increase in hardness due to precipitation hardening caused by the aging heat treatment. And, in order to maximize the effect of precipitation hardening, it is necessary to promote the formation and dispersion of intermetallic compounds, which are precipitates.

[0012] Based on the above viewpoints, the present inventors have attempted to optimize the additive elements in order to promote the precipitation of intermetallic compounds in Ag-Pd-Cu alloys. As a result, they have found that it is preferable to simultaneously add both Zn and Sn as essential additive elements. They have then optimized the ranges of the constituent elements and their composition ranges for Ag-Pd-Cu alloys containing Zn and Sn, and have arrived at the present invention.

[0013] That is, the present invention for solving the above-mentioned problems is a probe pin material made of an Ag-Pd-Cu alloy containing Ag, Pd, Cu, and essential additive elements Zn, Sn, and B, in which the Zn concentration is 0.5% by mass or more and 2.5% by mass or less, the Sn concentration is 0.5% by mass or more and 2.5% by mass or less, and the B concentration is 0.05% by mass or more and 0.5% by mass or less, and X, Y, and Z are located within a first region indicated by a polygon (A1-A2-A3-A4) obtained by surrounding with straight lines the following four points A1, A2, A3, and A4 in an XYZ pseudo ternary phase diagram, where X is the Ag concentration, Y is the Pd concentration, and Z is the Cu concentration + Zn concentration + Sn concentration + B concentration. ·First area Point A1 (X: 24% by mass, Y: 40% by mass, Z: 36% by mass) Point A2 (X: 34% by mass, Y: 40% by mass, Z: 26% by mass) Point A3 (X: 17% by mass, Y: 57% by mass, Z: 26% by mass) A4 point (X: 7% by mass, Y: 57% by mass, Z: 36% by mass)

[0014] The structure and characteristics of the probe pin material according to the present invention will be described in detail below. In this specification, an alloy consisting of only three elements, Ag, Pd, and Cu, is called an "Ag-Pd-Cu alloy." Also, an alloy containing Ag, Pd, Cu, and one or more other elements is called an "Ag-Pd-Cu alloy."

[0015] I. Configuration of the Probe Pin Material of the Present Invention As described above, the probe pin material according to the present invention is made of an Ag-Pd-Cu alloy. This Ag-Pd-Cu alloy is a six-element or higher alloy in which the essential elements Zn, Sn and B are added to an Ag-Pd-Cu alloy (ternary alloy). The constituent elements of the Ag-Pd-Cu alloy constituting the probe pin material according to the present invention and their composition ranges will be described below.

[0016] I-1. Constituent elements of the probe pin material according to the present invention (1) Ag, Pd, Cu The probe pin material according to the present invention uses an Ag-Pd-Cu alloy because the Ag-Pd-Cu alloy, which is the basic component, is expected to increase in hardness due to age hardening as described above, and is a conductive material with low resistance compared to precious metal-based alloys, etc. Therefore, Ag, Pd, and Cu are essential constituent elements that are fundamental to ensure the strength, hardness, electrical conductivity, etc. of the probe pin material.

[0017] (2) Zn, Sn In the present invention, in order to enhance the effect of age hardening in Ag-Pd-Cu alloys, both Zn and Sn are essential additive elements. Zn and Sn form intermetallic compounds (PdZn, PdSn) with Pd, respectively. As described above, Ag-Pd-Cu alloys exhibit precipitation hardening due to the PdCu phase (bcc), but further hardening is achieved by the formation of intermetallic compounds (PdZn, PdSn) with Zn and Sn. That is, the addition of both Zn and Sn improves the efficiency of precipitation hardening by aging heat treatment. As a result, in the present invention, the hardness increase by aging heat treatment is greater than that of conventional Ag-Pd-Cu alloys, and a hardness greater than that of the conventional technology can be exhibited.

[0018] As described above, in the Ag-Pd-Cu alloy of the present invention, it is necessary to add both Zn and Sn at the same time, and adding only one of them does not have much effect on increasing hardness. The above-mentioned prior art (Patent Document 6) by the applicant of the present application is also similar in that Zn and Sn are added to the Ag-Pd-Cu alloy, but the simultaneous addition of Zn and Sn is not essential in this prior art. In addition, the composition range of the basic Ag-Pd-Cu alloy is different in this prior art. This is because the prior art places more importance on improving bending resistance than hardness in the state after aging heat treatment.

[0019] (3)B In the present invention, in addition to Zn and Sn, B is also an essential additive element. B is added to ensure the basic strength and hardness of the alloy regardless of whether or not aging heat treatment is performed. In addition, B is present near the grain boundaries of the alloy, thereby imparting ductility to the alloy and contributing to ensuring workability.

[0020] (4) Other additive elements and unavoidable impurities The probe pin material according to the present invention is substantially made of an Ag-Pd-Cu alloy composed of Ag, Pd, Cu, Zn, Sn, and B. However, the probe pin material according to the present invention may contain other elements to the extent that the effects of the above-mentioned constituent elements are not impaired. Such other elements include Ti. Furthermore, the probe pin material according to the present invention may contain inevitable impurities. The inevitable impurities are elements that are mixed in from raw materials and manufacturing and processing equipment, and such elements may include Au, Co, Cr, Fe, Ir, Mg, Ni, Pt, Rh, Ru, Si, Zr, Al, Ca, etc., in addition to the above-mentioned other additive elements.

[0021] I-2. Alloy composition of the probe pin material according to the present invention In the Ag-Pd-Cu alloy of the present invention, the concentrations of the essential additive elements Zn, Sn, and B are set so as to optimize the increase in hardness due to aging heat treatment, and the concentrations of Ag, Pd, and Cu are determined taking into consideration these ranges. The concentration ranges of each additive element and the composition of the Ag-Pd-Cu alloy of the present invention are explained below.

[0022] (1) Zn and Sn concentrations The concentrations of Zn and Sn in the Ag-Pd-Cu alloy of the present invention are 0.5% by mass or more and 2.5% by mass or less for Zn and 0.5% by mass or less and 2.5% by mass or less for Sn. If the concentration of either is less than 0.5% by mass, it is difficult to generate an effective amount of intermetallic compounds for the development of precipitation hardening. Even if the concentration of either exceeds 2.5% by mass, there is no significant difference in hardness after aging heat treatment. If excessive amounts of Zn and Sn are added, intermetallic compounds may be generated at the stage before aging heat treatment (casting stage), which may result in a decrease in workability. The preferred concentrations of these additive elements are 0.7% by mass or more and 1.5% by mass or less for Zn and 1.0% by mass or more and 2.0% by mass or less for Sn.

[0023] (2) B concentration The B concentration is set to 0.05% by mass or more and 0.5% by mass or less. If it is less than 0.05% by mass, the above effect is not exhibited, and if it exceeds 0.5% by mass, the workability tends to decrease. The B concentration is more preferably set to 0.1% by mass or more and 0.3% by mass or less. Note that since B does not have the effect of promoting age hardening but has the above-mentioned auxiliary effect, the amount of B added is lower than that of Zn and Sn.

[0024] (3) Ag concentration (X), Pd concentration (Y), Cu concentration The Ag concentration, Pd concentration, and Cu concentration of the Ag-Pd-Cu alloy of the present invention are set within the optimum range for ensuring hardness and electrical conductivity, while keeping Zn, Sn, and B within the above ranges. Specifically, in the Ag-Pd-Cu alloy of the present invention, X, Y, and Z are located within the range of the first region shown by a polygon (A1-A2-A3-A4) that surrounds the four points A1, A2, A3, and A4 in the XYZ pseudo ternary phase diagram when the Ag concentration is X, the Pd concentration is Y, and the Cu concentration + Zn concentration + Sn concentration + B concentration is Z. Note that "within the range of the polygon that surrounds each point with a straight line" includes the case where each element concentration is on the line (on the side) and vertex of the polygon. In the Ag-Pd-Cu alloy of the present invention, the sum of the concentrations of Ag, Pd, and Cu in the first region (A1-A2-A3-A4) and the concentrations of the added elements Zn, Sn, and B is 100 mass %. Figure 1 shows the XYZ pseudo ternary phase diagram defined above and the first region (A1-A2-A3-A4).

[0025] ·First area Point A1 (X: 24% by mass, Y: 40% by mass, Z: 36% by mass) Point A2 (X: 34% by mass, Y: 40% by mass, Z: 26% by mass) Point A3 (X: 17% by mass, Y: 57% by mass, Z: 26% by mass) A4 point (X: 7% by mass, Y: 57% by mass, Z: 36% by mass)

[0026] The reason why X (Ag concentration), Y (Pd concentration), and Z (Cu concentration + Zn concentration + Sn concentration + B concentration) including Cu concentration are set within the above range is to make the hardness of the Ag-Pd-Cu based alloy after age hardening conform to the objective of the present invention (580 Hv or more) and to sufficiently precipitate the PdCu phase and the intermetallic compounds of PdZn and PdSn. If X, Y, and Z are outside the above range, the precipitation of the PdCu phase and the intermetallic compounds of PdZn and PdSn will be insufficient, making it difficult to obtain the desired hardness.

[0027] In the Ag-Pd-Cu alloy of the present invention, in which X (Ag concentration), Y (Pd concentration), and Z (Cu concentration + Zn concentration + Sn concentration + B concentration) are within the range of the first region, the hardness increase after aging heat treatment can be increased by adjusting the concentration of each constituent element. That is, it is preferable to set X (Ag concentration), Y (Pd concentration), and Z (Cu concentration + Zn concentration + Sn concentration + B concentration) within the range of the second region shown by a polygon (B1-B2-B3-B4) in which the following four points B1, B2, B3, and B4 are surrounded by straight lines in the same XYZ pseudo ternary phase diagram as above. Figure 2 shows this XYZ pseudo ternary phase diagram and the second region (B1-B2-B3-B4).

[0028] ·Second area Point B1 (X: 22% by mass, Y: 43% by mass, Z: 35% by mass) Point B2 (X: 30% by mass, Y: 42% by mass, Z: 28% by mass) Point B3 (X: 18% by mass, Y: 54% by mass, Z: 28% by mass) B4 points (X: 11% by mass, Y: 54% by mass, Z: 35% by mass)

[0029] Furthermore, it is particularly preferable to set X (Ag concentration), Y (Pd concentration), and Z (Cu concentration + Zn concentration + Sn concentration + B concentration) within the range of a third region shown by a polygon (C1-C2-C3-C4) that is drawn by straight lines between the following four points C1, C2, C3, and C4 in the XYZ pseudo ternary phase diagram. Figure 3 shows this XYZ pseudo ternary phase diagram and the third region (C1-C2-C3-C4).

[0030] ·Third area Point C1 (X: 20% by mass, Y: 46% by mass, Z: 34% by mass) Point C2 (X: 25% by mass, Y: 46% by mass, Z: 29% by mass) Point C3 (X: 20% by mass, Y: 51% by mass, Z: 29% by mass) Point C4 (X: 15% by mass, Y: 51% by mass, Z: 34% by mass)

[0031] (4) Concentrations of other added elements and unavoidable impurities In the Ag-Pd-Cu alloy of the present invention, when considering the inclusion of Ti, which is another additive element, its concentration is preferably 0.1 mass% or more and 1.3 mass% or less. The concentration of inevitable impurities is preferably 0.02 mass% or less in total, more preferably 0.005 mass% or less. When the above-mentioned other additive elements and inevitable impurities are detected in the probe pin material of the present invention, the total value of the concentrations of the essential constituent elements (Ag, Pd, Cu, Zn, Sn, B) and the concentrations of the other additive elements and inevitable impurities is 100 mass%, but X (Ag concentration), Y (Pd concentration), and Z (Cu concentration + Zn concentration + Sn concentration + B concentration) are within the range of the first to third regions.

[0032] The method of measuring the concentration of each constituent element (Ag concentration, Pd concentration, Cu concentration, Zn concentration, Sn concentration, B concentration) of the Ag-Pd-Cu alloy according to the present invention does not need to be particularly limited. As the measuring method, inductively coupled plasma emission spectrometry (ICP emission spectrometry) and X-ray fluorescence analysis (XRF analysis) can be applied. Furthermore, analytical methods such as energy dispersive X-ray analysis (EDX, EDS), electron probe microanalysis (EPMA), and energy dispersive wavelength dispersive X-ray analysis (WDX, WDS) can also be applied. By these analytical methods, the Ag concentration, Pd concentration, Cu concentration, Zn concentration, Sn concentration, and B concentration can be measured, respectively, and X, Y, and Z can be calculated. The same applies to the measurement of the concentrations of other additive elements and inevitable impurities.

[0033] II. Hardness and Morphology of the Probe Pin Material of the Present Invention The Ag-Pd-Cu alloy constituting the probe pin material according to the present invention exhibits a higher hardness than the conventional Ag-Pd-Cu alloy by the action of promoting the precipitation of intermetallic compounds by Zn and Sn as described above when subjected to aging heat treatment. Specifically, the Ag-Pd-Cu alloy having a composition within the range of the first region has a Vickers hardness of 580 Hv or more after aging heat treatment. The Ag-Pd-Cu alloy having a composition within the range of the second region has a hardness of 600 Hv or more after aging heat treatment. Furthermore, the Ag-Pd-Cu alloy having a composition within the range of the first region has a hardness of 620 Hv or more after aging heat treatment. The upper limit of the hardness after aging heat treatment is preferably about 700 Hv. This is because simple bending or the like may be performed even after aging heat treatment, and when considering the workability, it becomes difficult to use an excessively hard probe pin material.

[0034] The hardness of the probe pin material according to the present invention is due to the particle dispersion effect of the precipitates made of the intermetallic compounds. Here, the detailed composition (the ratio of each metal atom) of the intermetallic compounds precipitated in the Ag-Pd-Cu alloy of the present invention is not clear. However, the intermetallic compounds precipitated in the Ag-Pd-Cu alloy of the present invention are presumed to be PdCu phases containing Zn and Sn, that is, intermetallic compounds consisting of Zn, Sn, Pd, and Cu. Cu in the Ag-Pd-Cu alloy forms a PdCu phase with Pd, and Zn and Sn each combine with Pd to form an intermetallic compound (PdZn, PdSn). Therefore, the probe pin material according to the present invention has intermetallic compounds containing all of Pd, Cu, Zn, and Sn in the material structure.

[0035] Regarding the confirmation of the presence of intermetallic compounds in the material structure of Ag-Pd-Cu alloys, when the material structure of Ag-Pd-Cu alloys is observed by SEM or the like, dispersed phases with different hues are often observed, so that the dispersed phases can be assumed to be intermetallic compound phases. As a detailed identification method, element mapping is created by analytical means capable of surface analysis such as EDX, EDS, EPMA, etc., and if all elements of Zn, Sn, Pd, and Cu are present in the same area, it means that an intermetallic compound containing all of Pd, Cu, Zn, and Sn is present in that area. In particular, with regard to Zn and Sn, if there is a region where Zn and Sn are observed at a higher concentration than the concentration in the entire alloy, that region can be identified as an intermetallic compound phase.

[0036] As described above, the probe pin material made of an age-hardening alloy is processed into a wire or rod so as to have the shape of a probe pin or a shape close to the shape of a probe pin through cold working after melt casting. Then, it is hardened by aging heat treatment thereafter. The present invention can suitably handle such processing and heat treatment steps. This is because the Ag-Pd-Cu alloy of the present invention has a suitable hardness in terms of workability before aging heat treatment. Specifically, the probe pin material made of the Ag-Pd-Cu alloy of the present invention preferably has a Vickers hardness of 360 Hv or more and 450 Hv or less before aging treatment, more preferably 360 Hv or more and 410 Hv or less.

[0037] The probe pin material processed in the above steps before aging has the form of a straight wire or rod. In processing steps such as cold wire drawing, materials with poor workability will break in the worst case, but even if they do not, they are prone to deformation such as bending. The present invention, which has good workability, minimizes not only breakage but also bending deformation during processing. Specifically, the probe pin material according to the present invention can have a straightness of 2 mm / 1000 mm or less when in the form of a wire or rod. The straightness is the maximum value l of the distance l between the sample and the horizontal plane when a wire or rod of a predetermined length L is used as a sample and both ends of the sample are placed on a horizontal plane and the distance l between the sample and the horizontal plane is measured. max and the sample length L (lmax In the present invention, the maximum distance l when the predetermined length L is 1000 mm is max It is preferable that the thickness is 2 mm or less (2 mm / 1000 mm or less).

[0038] The Ag-Pd-Cu alloy of the present invention is naturally used for probe pin applications, but is often used in the form of a wire or rod for the probe pin. The dimensions of these forms are not particularly limited, but the wire diameter is often 50 μm to 1000 μm. The above-mentioned hardness of 580 Hv or more is preferably expressed when the wire is made into this wire.

[0039] III. Method for producing the probe pin material according to the present invention The probe pin material according to the present invention can be manufactured by producing an alloy ingot of the Ag-Pd-Cu alloy having the above-mentioned composition by melt casting, cold working the alloy ingot to a size and shape suitable for a probe pin, and then performing aging heat treatment. In the melt casting method, the alloy ingot is produced by casting after vacuum melting (reduced pressure melting) or atmospheric melting (atmosphere melting), and continuous casting and arc melting can also be applied. In addition, the alloy after casting may be hot worked and then cold worked.

[0040] The cold working process is a process for forming the Ag-Pd-Cu alloy ingot into the desired shape and dimensions, and for introducing processing strain into the alloy to obtain the strength and hardness required for a probe pin. The cold working method can be appropriately selected from rolling (including groove rolling), wire drawing, drawing and extrusion, etc., and these can be repeated multiple times or combined. The processing temperature is preferably 100°C or less.

[0041] The aging heat treatment is a process for obtaining a desired hardness by precipitating a PdCu ordered phase by heat treating the Ag-Pd-Cu alloy after cold working. The temperature of the aging heat treatment is preferably 300°C or higher and 580°C or lower. The treatment time is preferably 10 minutes or higher and 4 hours or lower.

[0042] The aging heat treatment is preferably performed in combination with a solution heat treatment. The solution heat treatment is a treatment in which the Ag-Pd-Cu alloy is heat-treated at a high temperature to bring it into a homogeneous supersaturated solid solution state, and is a treatment for favoring the precipitation of the PdCu ordered phase by the subsequent aging heat treatment. The heating temperature of the solution heat treatment of the Ag-Pd-Cu alloy of the present invention is preferably 650°C or higher and 950°C or lower. The cooling after heating is preferably rapid cooling such as water cooling.

[0043] The solution treatment can be performed multiple times. In the above-mentioned cold working process, wire drawing and the like can be performed multiple times, but a Ag-Pd-Cu alloy with optimal properties can be obtained by performing a solution treatment in the middle of these multiple cold working processes and performing an aging heat treatment after the final cold working. In this way, when performing a combination of cold working and solution treatment multiple times, it is preferable to perform the solution heat treatment while controlling the working rate (cross-sectional area reduction rate) in one cold working to be 12% or more and 99.99% or less.

[0044] The Ag-Pd-Cu alloy that has undergone the aging heat treatment has a suitable hardness of at least 580 Hv. After that, it can be made into a probe pin by performing final processing (cutting, bending, etc.) to obtain a detailed product shape. There is no limitation on the shape and dimensions of the probe pin, and it can be applied to a vertical probe pin, a cantilever probe pin, or a probe pin with a shape called a pogo pin. Effect of the Invention

[0045] As described above, the probe pin material according to the present invention is based on an Ag-Pd-Cu alloy, but contains additional elements (Zn, Sn) that have a large hardness-increasing effect due to the precipitation effect, thereby making it possible to produce a probe pin with a harder hardness than conventional materials. [Brief description of the drawings]

[0046] [Figure 1]1 is a diagram showing an XYZ pseudo ternary phase diagram (X: Ag concentration, Y: Pd concentration, Z: Cu concentration + Zn concentration + Sn concentration + B concentration) of the Ag-Pd-Cu alloy of the present invention and the range of the first region (A1-A2-A3-A4). [Diagram 2] 1 is a diagram showing an XYZ pseudo ternary phase diagram (X: Ag concentration, Y: Pd concentration, Z: Cu concentration + Zn concentration + Sn concentration + B concentration) of the Ag-Pd-Cu alloy of the present invention and the range of the second region (B1-B2-B3-B4). [Diagram 3] 1 is a diagram showing an XYZ pseudo ternary phase diagram (X: Ag concentration, Y: Pd concentration, Z: Cu concentration + Zn concentration + Sn concentration + B concentration) of the Ag-Pd-Cu alloy of the present invention and the range of the third region (C1-C2-C3-C4). [Figure 4] FIG. 2 is a diagram showing the composition of the Ag—Pd—Cu based alloy produced in the first embodiment in the form of an XYZ pseudo ternary phase diagram. [Diagram 5] FIG. 2 is a diagram for explaining a method for measuring the straightness of the Ag—Pd—Cu based alloy wire produced in the first embodiment. [Figure 6] FIG. 13 is a diagram showing the composition of the Ag—Pd—Cu based alloy produced in the second embodiment in the form of an XYZ pseudo ternary phase diagram. [Figure 7] FIG. 13 is an SEM image of the Ag-Pd-Cu alloy No. 37 produced in the second embodiment. [Figure 8] FIG. 13 is a diagram showing the results of EDS analysis (element mapping) of the Ag—Pd—Cu-based alloy No. 37 produced in the second embodiment. [Figure 9] FIG. 13 is a diagram showing the results of EDS analysis (point analysis) of the Ag—Pd—Cu-based alloy No. 37 produced in the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] First embodiment A preferred embodiment of the present invention will now be described. In this embodiment, probe pin materials made of Ag-Pd-Cu alloys of various compositions were manufactured and their hardness was measured.

[0048] In this embodiment, Ag, Pd, Cu, Zn, and Sn raw material ingots (99.9% or more purity) were mixed with B powder with a purity of 99.5%, and melt-cast to produce an Ag-Pd-Cu alloy ingot (diameter 6 mm). The concentration of each constituent element was analyzed by ICP for the produced alloy ingots of various compositions. The composition in the XYZ pseudo ternary phase diagram for the Ag-Pd-Cu alloy produced in the example of this embodiment is shown in FIG. 4. Note that FIG. 4 is a partially enlarged XYZ pseudo ternary phase diagram (X: 0% by mass to 50% by mass, Y: 30% by mass to 80% by mass, Z: 20% by mass to 70% by mass).

[0049] Next, Ag-Pd-Cu alloy ingots of various compositions were heat-treated at 850°C for 30 minutes, and then processed into 4 mm square rods by cold groove rolling. These rods were heated at 850°C for 30 minutes, then water-cooled and solution-treated. The rods were then cold-drawn into wires with a diameter of 0.7 mm, which were then subjected to aging heat treatment. The aging heat treatment was performed at a treatment temperature of 320 to 420°C for 60 minutes.

[0050] In this embodiment, as comparative examples for the Ag-Pd-Cu alloys of each example, wire rods of Ag-Pd-Cu ternary alloys without the addition of Zn, Sn, or B, and Ag-Pd-Cu alloys with only Zn or Sn added were also manufactured. Furthermore, wire rods of Ag-Pd-Cu alloys with In, Zr, Bi, or Cr added instead of Sn were also manufactured. The manufacturing process of the wire rods of these comparative examples was the same as that of the above examples.

[0051] [Hardness measurement] The hardness of the Ag-Pd-Cu alloy wires of various compositions manufactured above was measured. The hardness was measured using a micro Vickers hardness tester (HM-200, manufactured by Mitutoyo Corporation) with a load of 100 gf and a pressing time of 10 seconds. Measurements were taken at 13 locations on the vertical and horizontal lines intersecting at the center of the wire cross section, and the average value was taken as the hardness value. In addition, the hardness was measured before and after aging heat treatment for the wires (diameter 0.7 mm) after cold wire drawing, and the increase in hardness due to aging heat treatment was calculated from each hardness value.

[0052] [Processability evaluation] In this embodiment, the workability of the Ag-Pd-Cu alloy was also evaluated. The workability was evaluated based on the presence or absence of cracks during groove rolling and breaks during cold drawing in the above-mentioned wire processing step. Specifically, the wire (diameter 0.7 mm) was evaluated as pass (◯) when it could be processed into a wire without any cracks or breaks, the wire was evaluated as fail (△) when breaks occurred once or twice during cold drawing but a wire that could be processed into a sample was obtained, and the wire was evaluated as fail (×) when breaks occurred frequently and no wire could be produced at all.

[0053] [Elongation evaluation] Furthermore, the straightness of the wire (diameter 0.7 mm) after cold wire drawing (before aging heat treatment) was evaluated. The method for measuring the straightness was as shown in Figure 5. The wire was cut so that the length L of the sample wire was 1000 mm, and both ends of the sample were placed on a horizontal table. The distance l between the horizontal table and the sample was then measured, and the maximum value l was max In this embodiment, the evaluation criterion for straightness is max The evaluation criteria were set to ≦2 mm / 1000 mm, and cases where this criteria was met were marked as pass (◯), and cases where it was not met were marked as fail (×).

[0054] Table 1 shows the evaluation results regarding hardness, workability, and straightness of the Ag-Pd-Cu ternary alloy and the Ag-Pd-Cu based alloy probe pin materials manufactured in this embodiment.

[0055] [Table 1]

[0056] From Table 1, it can be seen that the probe pin materials made of Ag-Pd-Cu alloys of Examples 1 to 8 manufactured in this embodiment exhibit high hardness, with a Vickers hardness of 580 Hv or more after age hardening. The probe pin materials of these Examples showed a hardness increase of 200 Hv or more due to age hardening. It was also confirmed that the workability before the aging heat treatment was good and wire rods with good straightness could be manufactured.

[0057] However, if the concentration of either Zn or Sn exceeds 2.5 mass%, the workability into wire rod decreases, so the upper limit of these should be 2.5 mass% (Comparative Examples 1 and 2). Also, as in Comparative Examples 3 to 7, when only one of Zn and Sn is added in an appropriate amount, a hardness of about 570 Hv is shown, so a certain degree of high hardness can be expected. However, the hardness increase due to age hardening in these comparative examples is less than 200 Hv, which is insufficient in terms of maximizing the effect of intermetallic compound precipitation. Furthermore, it was confirmed that B is an additive element that affects workability. Since the workability deteriorates when B is not added, and also deteriorates when B is added excessively, the addition of B should be essential.

[0058] Moreover, the Ag-Pd-Cu ternary alloy probe pin material without any added elements generally had low hardness, remaining at around 500 Hv (Comparative Examples 9 to 12). In these comparative examples, the increase in hardness due to age hardening was large, as in the examples, but the hardness before aging was low, so the final hardness was significantly insufficient.

[0059] Furthermore, for Ag-Pd-Cu alloys in which In, Zr, Bi, and Cr are added together with Zn, some are expected to have high hardness, but the hardness increase is small and does not reach that of each example (Comparative Example 13, Comparative Example 16). Some alloys could not be processed due to cracking during groove rolling or breakage during cold drawing (Comparative Example 14, Comparative Example 15). Therefore, it can be said that the combination of Zn and Sn is suitable.

[0060] Second embodiment In this embodiment, the effect of increasing the hardness of the Ag-Pd-Cu alloy of the present invention was confirmed in detail within the composition ranges of the above-mentioned first to third regions. In this embodiment, the Zn concentration was set to about 1.0 mass%, the Sn concentration was set to about 1.4 mass%, and the B concentration was set to 0.15 mass%, and the concentrations of Ag, Pd, and Cu were adjusted to manufacture a probe pin material made of a wire of the Ag-Pd-Cu alloy.

[0061] The manufacturing process and manufacturing conditions of the Ag-Pd-Cu alloy wire of this embodiment were the same as those of the first embodiment. Then, the hardness of the wire cross section was measured in the same manner as in the first embodiment. The workability and elongation were also evaluated in the same manner as in the first embodiment. The evaluation results are shown in Table 2. FIG. 6 shows an XYZ pseudo ternary phase diagram showing the composition of the Ag-Pd-Cu alloy manufactured in this embodiment. FIG. 6 is a partially enlarged XYZ pseudo ternary phase diagram similar to FIG. 4. In FIG. 6, the composition of the sample in the first region shown in Table 2 is shown by "△", the composition of the sample in the second region is shown by "◯", and the composition of the sample in the third region is shown by "●".

[0062] [Table 2]

[0063] From Table 2, it was confirmed that all of the probe pin materials made of Ag-Pd-Cu alloy wires manufactured in the second embodiment had a hardness of 580 Hv or more after aging heat treatment. The alloys with compositions in the second region showed a hardness of 600 Hv or more. Furthermore, the alloys with compositions in the third region showed an extremely good hardness of 620 Hv or more. In the Ag-Pd-Cu alloys with compositions in the second and third regions, the hardness increase due to age hardening significantly exceeds 200 Hv. Considering that there is no significant difference between the hardness before age hardening and the first region, it can be said that the effect of age hardening is more favorably exhibited in the second and third regions. Even in such high-hardness probe pin materials, the hardness before aging heat treatment is not so large, so processing before aging heat treatment is easy. This can also be understood from the evaluation of workability.

[0064] The Ag-Pd-Cu alloy produced in this embodiment was observed for its material structure. A scanning electron microscope (SEM: JSM-IT700HR, manufactured by JEOL Ltd.) was used for the structure observation. In addition, elemental analysis of the observation area was performed simultaneously with the SEM observation using EDS (ULTIM MAX40, manufactured by Oxford Instruments) (accelerating voltage 15 kV). The structure analysis was performed on the cross section of the wire before and after aging treatment.

[0065] Figure 7 shows an SEM image of Ag-Pd-Cu alloy No. 37 as an example of the observation results. In Figure 7, the matrix phase and the intermetallic compound phase can be recognized by their light and dark shades, and the dark gray phase is the intermetallic compound. Figure 7 shows that the intermetallic compound phase increases and disperses due to the aging heat treatment. In addition, in this No. 37, intermetallic compounds are formed even before the aging heat treatment, although only in small amounts.

[0066] The results of element mapping analysis by EDS for the material structure of Example No. 37 are shown in FIG. 8. The results of point analysis performed on the matrix phase and the intermetallic compound phase are shown in FIG. 9. In the element mapping of FIG. 8, the points where the four elements Pd, Cu, Zn, and Sn are observed overlappingly indicate the presence of an intermetallic compound. This point can be clearly confirmed from the point analysis of FIG. 9, where the spectrum peaks of Zn and Sn are not observed in the matrix phase, but the spectrum peaks of the four elements Pd, Cu, Zn, and Sn are observed in the intermetallic compound. From this, it was confirmed that the Ag-Pd-Cu alloy of the present invention contains an intermetallic compound composed of Pd, Cu, Zn, and Sn. [Industrial Applicability]

[0067] As described above, the probe pin material according to the present invention exhibits a more efficient age hardening effect than ever before, thereby achieving high hardness. The probe pin material according to the present invention has excellent wear resistance due to the high hardness, and also takes into consideration processability. The present invention is applied to probe pins of probe cards for testing various electronic devices, semiconductor devices, power devices, etc. In particular, the present invention, which has excellent bending resistance, can be usefully applied to cantilever-type probe pins and probe pins in a shape called pogo pins.

Claims

1. A probe pin material made of an Ag-Pd-Cu alloy containing Ag, Pd, Cu, essential additive elements Zn, Sn, and B, and inevitable impurities, The Zn concentration is 0.5 mass% or more and 2.5 mass% or less, the Sn concentration is 0.5 mass% or more and 2.5 mass% or less, and the B concentration is 0.05 mass% or more and 0.5 mass% or less, X, Y, and Z are located within a first region defined by a polygon (A1-A2-A3-A4) defined by straight lines connecting four points A1, A2, A3, and A4 in an X-Y-Z pseudo ternary phase diagram, where X is the Ag concentration, Y is the Pd concentration, and Z is the Cu concentration + Zn concentration + Sn concentration + B concentration. A probe pin material having a Vickers hardness of 580 Hv or more. ・First area Point A1 (X: 24% by mass, Y: 40% by mass, Z: 36% by mass) Point A2 (X: 34% by mass, Y: 40% by mass, Z: 26% by mass) Point A3 (X: 17% by mass, Y: 57% by mass, Z: 26% by mass) A4 point (X: 7% by mass, Y: 57% by mass, Z: 36% by mass)

2. The probe pin material according to claim 1, wherein X, Y, and Z are located within a second region defined by a polygon (B1-B2-B3-B4) defined by straight lines connecting four points B1, B2, B3, and B4 in an X-Y-Z pseudo ternary phase diagram, where X is an Ag concentration, Y is a Pd concentration, and Z is a Cu concentration + Zn concentration + Sn concentration + B concentration. ・Second area Point B1 (X: 22% by mass, Y: 43% by mass, Z: 35% by mass) Point B2 (X: 30% by mass, Y: 42% by mass, Z: 28% by mass) Point B3 (X: 18% by mass, Y: 54% by mass, Z: 28% by mass) Point B4 (X: 11% by mass, Y: 54% by mass, Z: 35% by mass)

3. The probe pin material according to claim 1, wherein X, Y, and Z are located within a third region defined by a polygon (C1-C2-C3-C4) defined by straight lines connecting four points C1, C2, C3, and C4 in an X-Y-Z pseudo ternary phase diagram, where X is an Ag concentration, Y is a Pd concentration, and Z is a Cu concentration + Zn concentration + Sn concentration + B concentration. ・Third area Point C1 (X: 20% by mass, Y: 46% by mass, Z: 34% by mass) Point C2 (X: 25% by mass, Y: 46% by mass, Z: 29% by mass) Point C3 (X: 20% by mass, Y: 51% by mass, Z: 29% by mass) Point C4 (X: 15% by mass, Y: 51% by mass, Z: 34% by mass)

4. 2. The probe pin material according to claim 1, wherein the material structure has an intermetallic compound containing all of Pd, Cu, Zn and Sn.

5. A probe pin comprising the probe pin material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • JP1973078401A

  • High-strength silver-palladium alloy

    JP2001518980A

  • MATERIAL FOR PROBE PIN COMPOSED OF Ag-Pd-Cu-BASED ALLOY

    JP2023116833A

  • Probe pin

    JP4176133B1

  • Probe card with probe pin and probe pin

    JP4216823B2